Malay Local Wisdom Values in Elementary School Learning - Vany Sinthya; Zaka Hadikusuma Ramadan (Universitas Pendidikan Ganesha, 2021)
The implementation of local wisdom values involving teachers and students is not running optimally due to the impact of the Covid-19 pandemic. It causes learning not to run optimally. This study aims to analyze the implementation of Sunda local wisdom values in learning in elementary schools. The researcher used a qualitative approach with a descriptive method. The subjects of this study were 1 principal, 7 teachers and 16 students. Researchers made observations starting from grades 1 to 6 with representatives of 6 classes. Data collection techniques used by researchers in interviews, observation, documentation. The data analysis technique used is descriptive qualitative. The results showed that the value of Sunda local wisdom was implemented well in schools and every lesson. Five discounts of local Sunda wisdom are applied in learning, namely religious values, peace-loving values, cooperation values, tolerance values, and environmental care values. The value of Malay local wisdom is significant to be applied in schools so that students have good morals, character, and manners to behave and behave according to the culture in their environment.